The Representation of Reunion 212 in Indonesian Online Media - Nizar Ibnus (Universitas Ahmad Dahlan, 2019)
Reunion 212 which is the action of a series of previous actions was reported by many media in Indonesia. Each media portrays the action differently. This critical discourse analysis attempts to uncover the practice of power in Indonesian online media regarding the rally. Three reunion 212-related articles published on December 2, 2017 from each of CNN Indonesia.com and Republika Online were collected as the data of the study. Those online media were chosen as preliminary study informs that they frequently take different point of view whey they are reporting moslem or islamic related issues. The data collected were analyzed using van Dijk discourse analysis approach which consisted of text analysis, social cognition, and social context. The findings confirm that CNN Indonesia.com is more concerned about the adverse effects of the action and the purpose of the action which is considered politically charged, while Republika Online brings more humanist themes eventhough it also does not deny the potential political purpose behind the action. The themes are supported by certain lexical and discourse strategies such as word choice, theme choice, cohesion, and coherence. Moreover, the power practice is more visible in CNN Indonesia.com which attempts to convince readers that the action is bad and orientates itself more toward political purposes. While the news from Republika Online is more informative and only contains the positive side of the action.